Chemical pleurodesis with autologous blood and freeze-dried concentrated human thrombin improved spontaneous pneumothorax and thoracic endometriosis: The first case involving a pregnant woman - Ippei Yasuda; Takao Hidaka; Tae Kusabiraki; Keiko Kochi; Kuniaki Yasoshima; Kiyoshi Takagawa; Shigeru Saito (Elsevier, 2018)
Objective: Spontaneous pneumothorax combined with thoracic endometriosis is a rare condition during pregnancy. We present a case of chemical pleurodesis with autologous blood and freeze-dried concentrated human thrombin during pregnancy. Case report: This report presents a case of spontaneous pneumothorax combined with thoracic endometriosis that arose at 22 weeks' gestation in a 35-year-old female. The initial chest drainage was unsuccessful. At 25 weeks' gestation, video-assisted thoracoscopic surgery was performed and revealed endometriosis in the thoracic cavity. Since the leak persisted, chemical pleurodesis was performed with autologous blood and freeze-dried concentrated human thrombin at 28 weeks' gestation. The leak improved markedly and did not recur. Conclusion: This is the first case report about chemical pleurodesis with autologous blood and freeze-dried concentrated human thrombin during pregnancy. This procedure might contribute to the management of pneumothorax in pregnant women.